Calculation of the Mastoid Cell Volume of Infants From Computed Tomography Imaging. Issue 3 (May 2015) - Karahasanoglu, Aylin; Aksoy, Sema; Hocaoglu, Elif; Bayramoglu, Sibel; Inci, Ercan
<x xml:space="preserve">Abstract</x> Objective: The objective of this study was to calculate the mastoid cell volume of infants using computed tomography imaging. Methods: We calculated the mastoid cell volumes of 87 infants younger than 1 year classified into 4 age groups. Results: There were significant (P = 0.0001) differences in the ear mastoid cell volumes (cm3) among the 0- to 3-, 4- to 6-, 7- to 9-, and 10- to 12-month age groups. Generally, the mastoid cell volume increased with age. Conclusions: Mastoid cell volume correlates with the age of infants up to 1 year. We plan to expand this study and determine cutoff values for the mastoid cell volumes of infants.